2016
DOI: 10.1111/cns.12576
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of an Aminopropyl Carbazole Derivative P7C3‐A20 in Ischemic Stroke

Abstract: P7C3-A20 has neuroprotective effect in cerebral ischemia. The study contributes to the development of NAMPT activators against ischemic stroke and expands the horizon of the neuroprotective effect of aminopropyl carbazole chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 48 publications
(76 reference statements)
2
32
0
Order By: Relevance
“…Middle cerebral artery occlusion (MCAO) surgery in rats was performed as described [23]. The rats were anesthetized with a combination of ketamine (50 mg/kg), xylazine (2.6 mg/kg), and acepromazine (0.50 mg/kg) by intraperitoneal injection.…”
Section: Middle Cerebral Artery Occlusion Modelmentioning
confidence: 99%
“…Middle cerebral artery occlusion (MCAO) surgery in rats was performed as described [23]. The rats were anesthetized with a combination of ketamine (50 mg/kg), xylazine (2.6 mg/kg), and acepromazine (0.50 mg/kg) by intraperitoneal injection.…”
Section: Middle Cerebral Artery Occlusion Modelmentioning
confidence: 99%
“…Stem cells have the ability of self‐renewing and differentiating into various cell lineages, and stem cell‐based strategies hold promise in curing traumatic brain injury and stroke . Our group has done much work in identifying therapeutic targets and screening effective neuroprotective drugs against stroke . Recently, we have demonstrated that nicotinamide phosphoribosyltransferase‐NAD cascade which is particularly important for the proliferation, self‐renewal, and differentiation of neural stem cells can promote regenerative neurogenesis after ischemic stroke .…”
Section: Applications and Advantages Of Brain Organoid Technologymentioning
confidence: 99%
“…[40][41][42] Our group has done much work in identifying therapeutic targets and screening effective neuroprotective drugs against stroke. [43][44][45] Recently, we have demonstrated that nicotinamide phosphoribosyltransferase-NAD cascade which is particularly important for the proliferation, self-renewal, and differentiation of neural stem cells can promote regenerative neurogenesis after ischemic stroke. [46][47][48] In addition to promoting tissue regeneration by stimulating endogenous stem cells, progress in stem cell transplantation also enhances the development of regenerative medicine.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…Aged rats that underwent prolonged administration of P7C3 also performed better on cognitive tasks and exhibited decreased cell death in the hippocampus 17 . Subsequently, the neuroprotective effects of P7C3 and its derivative compounds have been further demonstrated in broad preclinical rodent models of CNS disease and injury, including environmental stress-related hippocampal cell death 18 20 , amyotrophic lateral sclerosis 21 , Parkinson’s disease 22 25 , traumatic brain injury 26 28 , peripheral nerve crush 29 , chemotherapy-induced peripheral neuropathy 30 , optic nerve injury 31 , 32 , Alzheimer’s disease 33 , stroke 34 36 , and recently expanded to acetaminophen-induced liver toxicity 37 . Mechanistically, P7C3 increases nicotinamide adenine dinucleotide (NAD) flux in mammalian cells under conditions of otherwise overwhelming energy crisis that would normally lead to cell death 38 .…”
Section: Introductionmentioning
confidence: 99%